Development of a reverse supply chain model for electronic waste incorporating transportation risk - Doan Thi Truc Linh; Yousef Amer; Sang- Heon Lee; Phan Nguyen Ky Phuc (Institut Teknologi Sepuluh Nopember, 2018)
The quantity of Electronic waste (E-waste) is considerably growing due to the rapid development of technology. To diminish the influences of E-waste to the environment and recover raw materials, the reverse supply chain (RSC) has been examined. Most research focuses on minimizing the total cost of the system, however, does not integrate risk factors related to RSC operation. Risks generally derive from transportation activity in E-waste RSC such as delays for pick up, breakdown of trucks, the uncertainty of dangerous materials which might lead to disruptions and higher cost. Therefore, this paper aims to develop a mathematical model for minimizing the total cost of E-waste RSC which integrates transportation risk. A mixed integer linear programming is utilized in the model and addressed by an optimization software. The results of the proposed model can determine the optimal locations and the amount of used products transported within the RSC network. The numerical example also demonstrates that the movement of materials or components in the RSC network is considerably affected by considering transportation risk. The suggested model can assist decision makers about establishing RSC network in which risk elements are incorporated.